Video Curriculum on Screening for the Social Determinants of Health - Melissa Klein; Andrew Beck; Robert Kahn; Adrienne Henize; Jennifer O'Toole; Alicia Alcamo; Daniel McLinden (Association of American Medical Colleges, 2013)
Abstract Introduction Social determinants of health (SDH) are emerging as a major barrier to the promotion of child health in the twenty-first century. The effects of poverty, including food insecurity, unsafe housing conditions, inadequate educational interventions, domestic violence, and limited access to medical care, have been linked to poor health and developmental outcomes in children. Many pediatric residents lack competence in identifying families that face social, economic, or environmental difficulties and feel inadequately prepared to counsel and refer patients and families to appropriate community resources due to their limited training during medical school and early residency years. Methods This curriculum was developed following a needs assessment and positive feedback obtained after a brief one-time educational experience with videotaped social history vignettes. Scripts for a series of appropriate and inappropriate video vignettes depicting typical scenarios of resident physicians screening for SDH in continuity clinic were developed, with clinic parents and resident physicians acting in their respective roles. A series of "Day in the Life" videos was also created to allow actual patients and families from the clinic tell their story of how screening, detection, and intervention impacted their family's lives. Residents experience this resource by attending the included didactic PowerPoint presentation, viewing the appropriate/inappropriate vignettes, engaging in group discussion, viewing the "Day in the Life" videos, and participating in a final discussion. Results The vast majority (> 95%) of participating residents strongly agreed/agreed that this education addressed important topics and included a good combination of both didactic and interactive components. Resident selfrated competence in screening for housing, benefits, and educational concerns significantly improved (p < 0.05 for each). Parents seen by residents who received this education reported that the resident was significantly more likely to screen for both domestic violence and depression. Although not significant, parents also recalled being screened more frequently for food insecurity, public benefits issues, housing, and educational needs. Discussion Many pediatric residents lack competence in counseling and referring patients and families to appropriate community resources. Additionally, the majority of pediatric residents were not raised in poverty, so they cannot build upon their past experiences. Through the use of these vignettes, videotaped first-hand accounts, and discussions, residents are better equipped to identify and aid families in need.